The Influence of CSR Practices on Hotel Images and Hotel Benefits in Bangladesh - Al Karim, Rashed (Journal of Technology Management and Business, 2022)
This study investigates how hotel Corporate Social Responsibility (CSR) practices influence hotel image and hotel benefits based on the tourist perception of Bangladesh using Elkington’s (1998) Triple Bottom Line (TBL) as a study framework. Data were collected by conducting survey using a structured questionnaire. A total of 295 tourist responses were accumulated using a convenient sampling technique in the 4 and 5-stars hotels from two major tourism-based cities in Bangladesh, namely Chattogram and Cox’s Bazar. The results revealed that hotel CSR practices (economic, social, and environmental) positively influence both the hotel image and hotel benefits in the Bangladesh hotel industry context. Finally, the findings of this study will aid in the planning and development of Bangladesh’s hotel industry and its long-term development.